Reciprocal Regulation of Shh Trafficking and H2O2 Levels via a Noncanonical BOC-Rac1 Pathway - Marion Thauvin; Irène Amblard; Christine Rampon; Aurélien Mourton; Isabelle Queguiner; Chenge Li; Arnaud Gautier; Alain Joliot; Michel Volovitch; Sophie Vriz (Antioxidants, 2022)
Among molecules that bridge environment, cell metabolism, and cell signaling, hydrogen peroxide (H2O2) recently appeared as an emerging but central player. Its level depends on cell metabolism and environment and was recently shown to play key roles during embryogenesis, contrasting with its long-established role in disease progression. We decided to explore whether the secreted morphogen Sonic hedgehog (Shh), known to be essential in a variety of biological processes ranging from embryonic development to adult tissue homeostasis and cancers, was part of these interactions. Here, we report that H2O2 levels control key steps of Shh delivery in cell culture: increased levels reduce primary secretion, stimulate endocytosis and accelerate delivery to recipient cells; in addition, physiological in vivo modulation of H2O2 levels changes Shh distribution and tissue patterning. Moreover, a feedback loop exists in which Shh trafficking controls H2O2 synthesis via a non-canonical BOC-Rac1 pathway, leading to cytoneme growth. Our findings reveal that Shh directly impacts its own distribution, thus providing a molecular explanation for the robustness of morphogenesis to both environmental insults and individual variability.